2018
DOI: 10.1371/journal.pntd.0006620
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in human-gut microbiome in relation to a placebo-controlled anthelminthic trial in Indonesia

Abstract: BackgroundMicrobiome studies suggest the presence of an interaction between the human gut microbiome and soil-transmitted helminth. Upon deworming, a complex interaction between the anthelminthic drug, helminths and microbiome composition might occur. To dissect this, we analyse the changes that take place in the gut bacteria profiles in samples from a double blind placebo controlled trial conducted in an area endemic for soil transmitted helminths in Indonesia.MethodsEither placebo or albendazole were given e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 42 publications
5
60
1
Order By: Relevance
“…This suggests that the environment in which the microbiota and STH exist (all the other co-factors, such as the diet, age, lifestyle, and other previous and current infections of the human host) may determine whether or not STH affect the gut microbiota. This could explain why the effects of STH on the gut microbiome have not been consistent between studies, even when examining the same STH species Rosa et al 2018;Martin et al 2018;Cooper et al 2013). Thereby we conclude that the effects of STH infections on the microbiota are dependent on the context of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the environment in which the microbiota and STH exist (all the other co-factors, such as the diet, age, lifestyle, and other previous and current infections of the human host) may determine whether or not STH affect the gut microbiota. This could explain why the effects of STH on the gut microbiome have not been consistent between studies, even when examining the same STH species Rosa et al 2018;Martin et al 2018;Cooper et al 2013). Thereby we conclude that the effects of STH infections on the microbiota are dependent on the context of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study can be found elsewhere. 8 In a previous paper, 5 we identified an effect of treatment on the microbiome composition in subjects who were infected at baseline and at follow up. This relationship was studied in the post-treatment samples, whereas the microbiome composition at baseline was not used.…”
Section: Introductionmentioning
confidence: 95%
“…Here, parameter is unidentifiable. Similar to (5), we apply the parameterization in the work of Guimarães and Lindrooth, 12 where the overdispersion is absorbed in the grand mean 0 such that −1 exp( 0 ) = −1 0 in the reference category. In contrast to the nonoverdispersed multinomial model, the intercepts of the overdispersed multinomial model do not cancel out.…”
Section: Overdispersed Multinomialmentioning
confidence: 99%
See 2 more Smart Citations